Inequities in cancer drug development in terms of unmet medical need. (June 2022) - Barrenho, Eliana; Halmai, Réka; Miraldo, Marisa; Tzintzun, Iván; Raïs Ali, Setti; Toulemon, Léa; Dupont, Jean-Claude K.; Rochaix, Lise
Abstract: This study measures inequality and inequity in the distribution of clinical trials on cancer drug development between 1996 and 2016, comparing the number of clinical trials with cancer need, proxied by prevalence, incidence, or survival rates for both rare and non-rare cancers. We leverage a unique global database of clinical trials activity and costs between 1996 and 2016, constructed for 227 different cancer types to measure for rare and non-rare cancers: i) inequalities and inequity of clinical trial activity, considering all trials as well as split by R&D stage; ii) inequalities and inequity in R&D investment proxied by trial enrollment and duration; iii) evolution of inequity over time. Inequalities are measured with concentration curves and indices and inequities measured with the health inequity index. We find four important results. First, we show pro-low need inequity across cancer types for both rare and non-rare cancers, for all need proxies. Second, we show inequity differs across R&D stages and between rare and non-rare cancers. The distribution of clinical trials for non-rare cancers disproportionately favors low-need non-rare cancers from earlier to later stages of R&D, whilst for rare cancers this only occurs in Phase 2 trials. Third, inequity analyses in R&D investment show that only trial enrollment for rare cancers and trial duration for non-rare cancers are disproportionately concentrated among low-need cancers. Finally, while pro-low need inequity has persisted between 1996 and 2016 for non-rare cancers, it has faded for rare cancers post-EU orphan drugs' legislation. Highlights: There are inequities in pharmaceutical R&D activity and investment targeting cancers. Inequity differs across R&D stages and between rare and non-rare cancers. Inequity has persisted between 1996 and 2016 for non-rare cancers. Inequity has faded for rare cancers the period post-EU orphan drugs' legislation.